Blockchain technology and the role of blockchain in uzbekistan (Texas Journal of Multidisciplinary Studies, 2022)
This article gives you a brief overview on blockchain technology and its benefits. There is talk about the development of blockchain in Uzbekistan and in what areas the blockchain can be widely used.